The Analysis of Cultural Contents in the Elt Textbook For Senior High School Students - Sabella Nisya Adelliya (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Language and culture have a close relationship, often described as being inextricably linked. Language is the primary means of communication that represents a person’s personality and culture. So, it can be said that the language used in daily communication is proven to define a culture. Learning a language is not enough to achieve proficiency in communication; it also requires an understanding of the cultural norms and values that shape the language and keep it in line with the culture. Therefore, it is essential to understand the relationship between culture and language to comprehend the extent to which they are intertwined in everyday life. It is said that someone who learns a language without also learning and understanding the culture is considered at risk of not becoming fluent in the language.
Repo 17 Juli 2026_ Rudy K Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: The Analysis of Cultural